2009
DOI: 10.1007/s10549-009-0310-8
|View full text |Cite
|
Sign up to set email alerts
|

Lapatinib plus capecitabine versus capecitabine alone for HER2+ (ErbB2+) metastatic breast cancer: quality-of-life assessment

Abstract: The randomized phase III trial EGF100151 demonstrated that the combination of lapatinib plus capecitabine (L + C) significantly improved time to progression (TTP) compared with capecitabine alone (C) in heavily pretreated patients with HER2+ (ErbB2+) advanced or metastatic breast cancer. This analysis assessed the effects of study treatments on quality of life (QOL) among patients in EGF100151. Quality of life was assessed using the Functional Assessment of Cancer Therapy-Breast (FACT-B) and EuroQoL (EQ-5D) qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 31 publications
1
44
0
1
Order By: Relevance
“…Оценка связи между КЖ и ответом опухоли на лечение у больных онкологическими заболеваниями разной локали-зации, например раком молочной железы и почечно-кле-точным раком, изучалась в ряде клинических исследований [23,21,19,20,7]. Было показано, что у пациентов с медлен-ным прогрессированием опухолевого заболевания, продол-жающих лечение, КЖ стабильное или снижается медленнее, чем у пациентов с быстрым прогрессированием.…”
unclassified
“…Оценка связи между КЖ и ответом опухоли на лечение у больных онкологическими заболеваниями разной локали-зации, например раком молочной железы и почечно-кле-точным раком, изучалась в ряде клинических исследований [23,21,19,20,7]. Было показано, что у пациентов с медлен-ным прогрессированием опухолевого заболевания, продол-жающих лечение, КЖ стабильное или снижается медленнее, чем у пациентов с быстрым прогрессированием.…”
unclassified
“…[10][11][12][13] The study that reported the highest value (0.75) also estimated a value of 0.51 for patients receiving palliative care, thus indicating that individuals with terminal disease were not included in the cohort with mBC. 10 The lowest value (0.55) was reported in a study of patients receiving palliative care.…”
Section: -14mentioning
confidence: 99%
“…14 • A single study followed up patients receiving treatment for mBC and showed little change from baseline after 6 months of treatment with either capecitabine alone or capecitabine with lapatinib. 13 …”
Section: -14mentioning
confidence: 99%
“…Inputs and their sources are presented in Table 1. 14,18,[20][21][22][23][24][25] Two clinical studies formed the body of evidence to support the current cost-effectiveness analysis. Those were the EGF100151 and GBG 26/BIG 3-05 clinical trials, which demonstrated the clinical benefits of adding HER2-targeted therapy with lapatinib or trastuzumab to capecitabine monotherapy in patients with MBC who had progressed while receiving trastuzumab.…”
Section: Model Structure and Parametersmentioning
confidence: 99%
“…24 Estimated decrements in utility associated with progression were 32% (0.22 in absolute terms) using data from a study of societal preferences for different stages of MBC. 25 …”
Section: Model Structure and Parametersmentioning
confidence: 99%